Suggested Sustainable Medical and Environmental Uses of Melanin Pigment From Halotolerant Black Yeast Hortaea werneckii AS1 - Elsayis, Asmaa; Hassan, Sahar W. M.; Ghanem, Khaled M.; Khairy, Heba (Frontiers in Microbiology, 2022)
The marine ecosystem is a complex niche with unique environmental circumstances. Microbial communities from the sea are one of the main origins of compounds with tremendous capabilities. Marine yeasts have the ability to produce secondary metabolites that are architecturally distinct from those found in terrestrial species. Melanin pigment synthesized by marine halotolerant black yeast Hortaea werneckii AS1 isolated from Mediterranean salt lakes in Alexandria, Egypt was found to exert a radical scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) with an IC50 of 61.38 μg/ml. Furthermore, it showed no cytotoxicity toward human skin fibroblast cell line (HSF) with an IC50 value above 0.1 mg/ml. The antimicrobial capability of the pigment was revealed against the tested number of bacterial and fungal strains with the highest inhibition zone of 25 mm against Aeromonas sp. and a growth inhibition percentage up to 63.6% against Aspergillus niger. From an environmental impact point of view, the pigment disclosed a heavy metal removal efficiency of 85.7, 84.8, and 81.5% for Pb2+, Cd2+, and Ni2+, respectively, at 100 mg/L metal concentration. The previously mentioned results suggested melanin from H. werneckii AS1 as a promising biocompatible candidate in various medical, cosmetics, pharmaceutical, and environmental applications.